Application of high resolution remote sensing to detect and map the pasture weed Paterson’s curse (Echium plantagineum) in Western Australia - McIntyre, Daniel Lester (Curtin University, 2015)
This study investigated the utility of three types of remotely sensed data (field spectroscopy, airborne multispectral and satellite hyperspectral) for detecting and mapping Paterson’s curse (Echium plantagineum) in the Wheatbelt Region of Western Australia. Using different classification, statistical and quantitative validation approaches, the study found that spectral resolution and timing of image capture were the most important factors for discriminating Paterson’s curse and producing acceptable levels of mapping accuracy.